PRELIMINARY PHYTOCHEMICAL ANALYSIS OF WHOLE PLANT POWDER OF INDONEESIELLA ECHIOIDES (L.) SREEM. - M, *Rashmi; Sara Monsy, Oommen; V V, Shincymol (International Journal of Ayurveda and Pharma Research, 2017)
The plant Indoneesiella echioides (L.) Sreem. belonging to the family Acanthaceae, is a less known medicinal plant widely distributed in the Tropical India and Srilanka. The only mentioning of this drug is in the Hortus Malabaricus, a treatise on the plant wealth of Malabar during the 17th century. The reference depicted is for fever and poison indicating the time old application of the drug by traditional Ayurvedic practitioners. The drug is neither included in Ayurvedic pharmacopeia nor currently been used in Ayurvedic practice. Research works of the drug is done mostly with extracts of leaves and aerial parts. This paper deals with the preliminary phytochemical analysis of the whole plant powder. Apart from the available results of qualitative analysis, quantitative determination of fiber content, tannin content, total sugars, reducing sugars, phenols, extractive values and successive solvent extraction of the whole plant powder has been done in this study. The results obtained for the quantitative determination of tannins, total sugars, reducing sugars and phenols were 3.187%, 10.99%, 4.11% and 27.979 microgram/gram respectively. Variations were noted in the physico-chemical parameters such as total ash (6.77%), moisture content (9.55%) and crude fiber content (50.866%) comparing to the corresponding values of leaves extract. The influence of regional climatic conditions, (Desapradhanyata) is also evident from the study. Among the extractive values, water soluble extractives exceeded the alcohol soluble extractives which revalidate the usage of water based formulations in Ayurvedic science.